Development of Rapid UV Spectrophotometric Method for the Estimation of Efavirenz in Formulations - Y. Anand Kumar; N. Rama Rao (E-Journal of Chemistry)
Simple, sensitive, accurate, precise and rapid ultraviolet (UV) spectrophotometric method was developed for the estimation of efavirenz in pure form, its formulations and stability samples. For the estimation of efavirenz, solvent system employed was 1% w/v sodium lauryl sulphate (SLS) and wavelength of detection (λdet) was 247 nm. The developed method was used to estimate the total drug content in two commercially available oral formulations of efavirenz and recovery studies were also carried out. Sample recovery in both the formulations using the above method was in good agreement with their respective labeled claims, thus suggesting the validity of the method and non-interference of formulation excipients in the estimation. The developed method was found to be stability specific and were validated as per ICH guidelines-2005, USP-2000 and statistical methods.